Peran Humas Kemendikbudristek dalam Upaya Transparansi Informasi Program Bantuan Operasional Sekolah (BOS) - Salpiati, Emi; Toni, Ahmad; Witarti, Denik Iswardani (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2025)
School Operational Assistance Fund (BOS) is a government program aimed at improving the quality of primary and secondary education. Transparency in the management of the BOS funds has become crucial to the accountability and effectiveness of the program. The aim of this study is to explain the transparency efforts of the Humas Kemendikbudristek in managing information related to the use of the BOS funds. The purpose of this research is to know and explain the efforts of Kemendikkbudrsitek in transparency of information concerning the management of the Bos fund. This research uses qualitative methods with a descriptive approach. Data collection techniques are done through literature studies. Data is analyzed using Miles and Huberman model. The results of the research showed that Kemendikbudristek has made various efforts to improve the transparency of information related to the use of BOS funds. These efforts include: publication of information on the official website bos.kemdikbud.go.id, creation of infographics and video education, implementation of socialization and workshops, use of social media, public information request service by information and documentation managers and provision of complaints channels through the integrated service unit Kemendikbudristek. Nevertheless, there are still some weaknesses in the transparency of information, such as the lack of detailed information on how the BOSS funds are used by each BOS fund recipient school as well as lack of public participation in monitoring the use of BOSS. The findings also highlighted the need for improved training of school managers to avoid continuous misuse of BOSS funds, simplification of information systems, and more effective strategies to involve the public in monitoring the use of BOS funds. The study provides recommendations for improvement of information transparency policies and practices to improve accountability and efficiency of public fund management in the education sector.